The thermomechanical environment and the microstructure of an injection moulded polypropylene copolymer - Viana, J. C. (2002)
The microstructure of an injection moulding propylene copolymer is varied through systematic changes on the processing conditions (melt and mould temperatures and injection flow rate). The skin-core structure was characterised by several experimental techniques. The skin ratio was assessed by polarised light microscopy. The morphological features of the skin layer (level of crystalline phase orientation, degree of crystallinity, ...- phase content and double texture) were evaluated by wide-angle X-ray diffraction. The core features (degree of crystallinity and lamella thickness) were assessed by differential scanning calorimetry. The thermomechanical environment imposed during processing was characterised by mould filling simulations. The thermal and shear stress levels were evaluated by a cooling index and the wall shear stress. The results show the relationship between these and the microstructural features. The microstructure development is then interpreted considering the constrictions imposed during processing, being assessed by thermomechanical indices. Furthermore, the direct connections between these indices and the degree of crystallinity of the core and the level of orientation of the skin are verified.